2012
DOI: 10.1590/s1807-76922012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of market efficiency in Argentina, Brazil and Chile: an event study of mergers and acquisitions

Abstract: This paper presents an investigation into the relationship between the announcement of mergers and acquisitions, the existence of positive abnormal returns for shares of these firms, and market efficiency in Argentina, Brazil and Chile. Statistically significant Standardized Abnormal Returns were present in the event announcement and the following days in Argentina and Chile and on the event day in Brazil, confirming value creation signaling. Furthermore, the significance of abnormal returns in the event windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(30 reference statements)
0
5
0
1
Order By: Relevance
“…Table 3 shows a positive AAR for 41 days of the event window, for 41 days event window there were 8 days of significant AAR positive before the announcement and 5 days of a significant positive AAR before the announcement. A positive value in a semi-strong market will try to adjust to the right price level (Simões et al, 2012). As discussed in Section 4.2 a few days before the announcement there is already a significant positive AAR and after the announcement there are at T+1, T+8, T+10, T+15, and T+16.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Table 3 shows a positive AAR for 41 days of the event window, for 41 days event window there were 8 days of significant AAR positive before the announcement and 5 days of a significant positive AAR before the announcement. A positive value in a semi-strong market will try to adjust to the right price level (Simões et al, 2012). As discussed in Section 4.2 a few days before the announcement there is already a significant positive AAR and after the announcement there are at T+1, T+8, T+10, T+15, and T+16.…”
Section: Discussionmentioning
confidence: 93%
“…There is no AAR after the announcement because before the announcement there is already AAR where this causes when the announcement of the stock price has overpriced, so after the announcement there is no AAR. As previously explained, prices that are over-priced or under-priced will try to adjust to the right price level (Simões et al, 2012). The absence of AAR after the announcement gives the effect that there is no CAAR after the announcement.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A significant amount of literature gives facilitation to know about the effect of M&A on stock returns (Gopalaswamy, Acharya & Malik, 2008;Simões, Macedo-Soares, Klotzle & Pinto, 2012). It also gives assistance in order to know that how target and bidder firms are affected by it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The abnormal returns of the shares of both the acquired and the acquiring companies are positive and statistically significant, where the ones of the acquired companies (average of 10.82% and median of 6.39%) are larger than those of the acquiring companies (average of 3.38% and median of 3.52%). Simões et al (2012) developed a study comparing the abnormal returns of stocks of companies from different sectors that were involved in mergers and acquisitions in Brazil, Argentina and Chile, by means of a robust event study. They concluded that an increase took place in Brazil, represented by abnormal returns during the days of the event, while in Argentina and Chile, the subsequent abnormal returns of the days of the announcement were not significant.…”
Section: Mergers and Acquisitions As Value Creation Strategiesmentioning
confidence: 99%